PENGARUH PROMOSI DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA ONLINE SHOP AA_SPEEDSHOP - Winarni, Silvia; Witarsa, Witarsa; Budiman, Jumardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThis thesis is entitled "The Effect of Promotion and Service Quality on Consumer Purchase Decisions at the AA_SPEEDSHOP Online Shop". The problem in this research is "How do promotions and service quality affect consumer purchasing decisions at the AA_SPEEDSHOP online shop". The research method used is descriptive method. The form of research is quantitative description. Data collection techniques in this research are: indirect communication with data collection tools, questionnaires, documentary studies with data collection tools, data archives. The results of the study are: from the results of the research the influence of promotion and service quality have a significant effect on consumer purchasing decisions at the online shop AA_SPEEDSHOP and in terms of sub-problems, it can be concluded that: 1) Promotion has a significant effect on consumer purchasing decisions at the online shop AA_SPEEDSHOP. 2) There is an influence partial promotion on consumer purchasing decisions at the online shop AA.3) There is a partial effect of service quality on consumer purchasing decisions at the online shop AA_SPEEDSHOP.4) There is a simultaneous effect of promotion and service quality on consumer purchasing decisions at the online shop AA_SPEEDSHOP, the results of calculations using the help of SPSS version 18 obtained that this equation model has a significance value of 0.000 0.05. 5) Promotion and service quality variables simultaneously have a significant effect on the dependent variable of Consumer Purchase Decisions at the online shop AA_SPEEDSHOP.Keyword : Promotion, Service Quality, Consumer Purchase Decision on online shop AA_SPEEDSHOP